ISLAMIC RELIGIOUS EDUCATION IN SHAPING CHARACTER IN HIGHER EDUCATION: Indonesia - Nurlela; Evi Gusliana (STIT Pringsewu, 2022)
AbstractCharacter formation is associated with the term ethics, morality, and or values related to moral strength, connoting